Bridgeless single stage AC/DC converter with power factor correction - Anurag Sharma; Rajesh Gupta (Institute of Advanced Engineering and Science, 2022)
This research paper proposes a novel bridgeless single-stage isolated converter with power factor correction and load voltage control. The proposed converter reduces the input diode bridge requirement with reduced passive components and provides a unidirectional flow of power to the load. The single-stage design reduces the use of an electrolytic capacitor, which improves reliability and reduces the size of the converter. The proposed control method is based on a single proportional integral (PI) controller to achieve both power factor correction and input current control. The proposed bridgeless converter is suitable for electric vehicle (EV) charging. A simulation study is performed on the MATLAB/Simulink to verify the effectiveness of the proposed converter. The converter is implemented in the laboratory to obtain the experimental results using typhoon hardware in the loop (HIL) based real time simulator.